Menuju Dunia Kerja yang Inklusif bagi Penyandang Disabilitas : Tinjauan Laborem Exercens Art. 22 - Angela Florida Mau; Teresia Noiman Derung (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article examines the importance of creating an inclusive workplace for persons with disabilities from the perspective of the encyclical Laborem Exercens, which emphasizes the value and dignity of human beings in the context of work. Pope John Paul II asserts that work is a fundamental right of every individual, including persons with disabilities, enabling them to fully participate in society and develop their potential through employment. The aim of this article is to explore how the principles of Laborem Exercens can be implemented to create a fair, flexible, and accommodating workplace for persons with disabilities. The methodology employed in this article involves a literature review of the texts of Laborem Exercens and various sources related to inclusive policies, physical adjustments, and the use of assistive technologies in the workplace. This article also highlights the importance of collaboration among governments, companies, and communities as a key factor in establishing productive and empowering workplaces for persons with disabilities. Providing accessible facilities, flexible policies, and awareness training for managers and colleagues are proposed as concrete steps to realize an inclusive workplace. Achieving an inclusive work environment requires a collective commitment to respecting the dignity and rights of persons with disabilities, which, in turn, will improve their quality of life and contribute to the overall welfare of society. Implementing the values outlined in Laborem Exercens represents a significant step toward a more just, equitable, and inclusive working world.